Kualitas cracker cibi sebagai alternatif cemilan sehat - Fitri Yani Arbie; Novian Swasono Hadi; Denny Indra Setiawan; Rahma Labatjo; M Anas Anasiru (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
Non-Communicable Diseases (NCD) is the leading cause of death globally. One recommended strategy for improving food quality in preventing obesity and NCD is fish consumption. The selection of biscuit products